Legal Protection For Bus Passenger Consumers (Case Study of Bus Accidents in Guci, Tegal) - Thoriq Umam Farisy; Andriyanto Adhi Nugroho (Dinasti Research, 2024)
Public transportation, particularly buses, plays a vital role in community mobilization due to their flexibility and accessibility. While public transportation offers many benefits, its operation isn't always flawless, as evidenced by the continued occurrence of public transportation accidents, especially involving buses. This research aims to investigate the legal protection available to consumers who experience bus accidents and determine the responsibility of bus business operators towards accident victims in Guci, Tegal. The research employs a normative legal method (normative juridical) supplemented with interviews. The approach utilizes both a statutory approach and a case approach. The form of legal protection in the event of a bus accident has been regulated in the UUPK and UULLAJ. In this case, the PO Mitra Duta Sejati has not fulfilled its full responsibility because there is still one of the victims whose rights have not been fulfilled, namely the right to receive road maintenance when injured as a result of the accident and compensation to the families of the victims who died, this is contrary to paragraph 235 (1) and (2) UULLAJ. Therefore, the victim's family has the right to receive compensation from the PO Mitra Duta Sejati. The amount of compensation can be obtained from a court decision or amicably by way of agreement between both parties, this provision is based on article 236 paragraphs (1) and (2) UULLAJ. With this research, it is hoped that if passengers experience a bus accident, they will be able to know the form of legal protection and the form of responsibility of business actors.